1985
DOI: 10.1002/1097-0142(19850415)55:8<1753::aid-cncr2820550823>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of lymph-vascular space invasion in stage I endometrial cancer

Abstract: Surgical specimens from 111 patients with Stage I endometrial cancer were reviewed for the presence of lymph‐vascular space invasion by tumor cells. Lymph‐vascular space invasion was noted in 16 cases, and occurred most frequently in poorly differentiated tumors with deep myometrial penetration. Tumor recurrence developed in 44% of patients whose tumors demonstrated lymph‐vascular space invasion as opposed to only 2% of patients without this finding (p < 0.001). Of seven patients with lymph‐vascular space inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
4

Year Published

1989
1989
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(49 citation statements)
references
References 11 publications
4
41
0
4
Order By: Relevance
“…This seems to be due to the undifferentiated component of the histology. The median number of removed pelvic LNs was 16 (range, [15][16][17][18][19][20][21][22][23][24][25][26][27], the median number of removed para-aortic LNs was 8 (range, 4-30), and the median number of positive paraaortic LNs was 1 (range, 1-4). All patients had FIGO stage IIIC2 disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This seems to be due to the undifferentiated component of the histology. The median number of removed pelvic LNs was 16 (range, [15][16][17][18][19][20][21][22][23][24][25][26][27], the median number of removed para-aortic LNs was 8 (range, 4-30), and the median number of positive paraaortic LNs was 1 (range, 1-4). All patients had FIGO stage IIIC2 disease.…”
Section: Resultsmentioning
confidence: 99%
“…19 Tumor cells first develop the capacity for local tissue invasion and then spread through gaps between endothelial cells into the lymph-vascular space of the stroma, and, once LVSI has occurred, tumor cells have the potential for metastatic spread to other sites. 20 LVSI may lead to tumor emboli invading pelvic and para-aortic LNs.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of LVSI in patients with endometrial cancer is reported to be about 25% when all the stages and tumor grades are included [11,14]. In previous studies, the incidence of LVSI in clinical stage I was 14%-16% [8,9,15] and it was 15.5%-32.6% in clinical stages I and II [3,16]. The incidence of LVSI was 4.3% in surgical stages I and II [17] and it was 24.6% to 34.4% when all the surgical stages were included [18,19].…”
Section: Discussionmentioning
confidence: 98%
“…Once LVSI has occurred, the tumor cells theoretically have the potential to metastasize to regional lymph nodes or further. Thus, LVSI has been noted as an important prognostic factor that is signifi cantly correlated with nodal metastases, tumor recurrence, and patient survival [1,2,8]. The fi ndings of previous studies have been contradictory with respect to the significance of LVSI as an independent prognostic factor.…”
mentioning
confidence: 99%
“…Extrauterine factors include adnexal involvement, intraperitoneal metastasis, positive peritoneal cytology (13,14) and pelvic and para-aortic lymph node metastasis (7,15). Patients with no evidence of extrauterine disease, no cervical involvement and no evidence of vascular invasion are at low overall risk of recurrence.…”
Section: Introductionmentioning
confidence: 99%